2017
DOI: 10.7196/ajhpe.2017.v9i1.739
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of high-fidelity simulation: Nurse educators’ perceptions and experiences at a school of nursing in a resource-limited setting

Abstract: Background. Simulations are defined as situations where models are used for practice and to gain experience that will enhance students' practical skills. The use of simulations in clinical skills training can stimulate deep learning and help students to bridge the gap between theory and practice in nursing. This has been revealed in many studies where simulations positively impacted on clinical decision-making and patient care, and there has been great interest in the use of simulation in nurse training. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 11 publications
1
24
0
Order By: Relevance
“…While simulation‐based education has increased in extent and scope in many nurse education programs in Europe and in the United States, the literature reveals a lack of implementation and research linked to simulation as a pedagogic method in low‐resource settings (Livingston et al., 2014; Okrainec et al., 2009; Tansley et al., 2016). Although a few studies addressing simulation‐based education within nurse education programs in sub‐Saharan Africa can be found (Munangatire & Naidoo, 2017; Welman & Spies, 2016), the evidence base remains scarce.…”
Section: Background: Simulation‐based Educationmentioning
confidence: 99%
“…While simulation‐based education has increased in extent and scope in many nurse education programs in Europe and in the United States, the literature reveals a lack of implementation and research linked to simulation as a pedagogic method in low‐resource settings (Livingston et al., 2014; Okrainec et al., 2009; Tansley et al., 2016). Although a few studies addressing simulation‐based education within nurse education programs in sub‐Saharan Africa can be found (Munangatire & Naidoo, 2017; Welman & Spies, 2016), the evidence base remains scarce.…”
Section: Background: Simulation‐based Educationmentioning
confidence: 99%
“…To increase the likelihood of positive outcomes, formal training, appropriate technical support and resources for SLE educators are needed (Boese et al , 2013). Munangatire and Naidoo (2017) reported that whilst many educators are supportive of the adoption of the use of simulation as an effective teaching tool, if they are not given adequate direction for its implementation, they can be left feeling frustrated and disappointed with their performance. Given a predictable flow on effect, learning outcomes may not be met.…”
Section: Repetitionmentioning
confidence: 99%
“…In the healthcare sector, a simulation called High-Fidelity Simulation (HFS) is used to teach students and train teams. Numerous studies ( [13], [14], [15], [16]) evaluate the impact of these exercises on students' skills and on their ability to work in teams [13]. Static mannequins, role playing, CPR mannequins, and other techniques have also been utilized for education [17].…”
Section: High Fidelity Simulation In Healthcarementioning
confidence: 99%